Cohort profile: The prospective study on Chinese elderly with multimorbidity in primary care in Hong Kong. Issue 2 (20th February 2020) - Zhang, Dexing; Sit, Regina Wing Shan; Wong, Carmen; Zou, Dan; Mercer, Stewart W; Johnston, Marjorie C; Wong, Samuel Yeung Shan
Abstract : Purpose: This is an ongoing prospective cohort aiming to examine the biopsychosocial health profiles and predictors of health outcomes of older patients with multimorbidity in primary care in Hong Kong. Participants: From April 2016 to October 2017, 1077 patients aged 60+ years with at least two chronic diseases were recruited in four public primary care clinics in the New Territories East Region of Hong Kong. Findings to date: After weighting, the patients had 4.1 (1.8) chronic conditions and 2.5 (1.9) medications on average; 37% forgot taking medication sometimes; 71% rated their health as fair or poor; 17% were frail; 73% reported one (21%) or two or more (52%) body pain areas; 62% were overweight/obese; 23% reported chewing difficulty, 18% reported incontinence; 36% had current stage 1/2 hypertension; 38% had handgrip strength below the cut-off; 10% screened positive in sarcopenia; 17% had mild or severer cognitive impairment; 17% had mild to severe depression; 16% had mild to severe anxiety; 50% had subthreshold to severe insomnia; 28% indicated being lonely; 12% needed help in at least one out of the five daily functions and the EuroQoL-5-Dimensions-5-Level index score was 0.81 (0.20) and its Visual Analogue Scale (VAS) score was 67.6 (14.6). In the past 12 months, 17% were hospitalised, 92% attended general outpatient clinics, 70% attended specialist outpatient clinics and 10% used elderly daycare centre services, the median out-of-pocket health cost was HK$1000 (US$150). Female and male patients showed significant differences in many biopsychosocial health aspects. Future plans: With assessments and clinical data, the cohort can be used for understanding longitudinal trajectories of biopsychosocial health profiles of Chinese older patients with multimorbidity in primary care. We are also initially planning cohort studies on factors associated with various health outcomes, as well as quality of life and healthcare use. Cohort registration number: ChiCTR-OIC-16008477